Pengaruh penyuluhan terhadap peningkatan pengetahuan dan keputusan menggunakan kontrasepsi pada unmet need keluarga berencana di Umbularjo Kota Yogyakarta - Rahmawati Rahmawati; Endah Marianingsih Theresia; Dyah Noviawati Setya Arum (Jurnal Kesehatan Ibu dan Anak, 2012)
The growth of the population in Indonesia was always increasing, by a growth rate of 2.6 deaths per year. Family planning has been able to reduce the population growth rate from 2.4% to 1.9% in a rational way. Based on RISKESDAS/ Basic Medical Research in 2010, the use of family planning is known only 53.9% in married women age 19 years. Nationally, there were still 19% of married women during reproductive age who did not use Family planning to prevent or delay pregnancy, and there were 27.1% who previously used family planning but now did not use it after then was nationally detected by 14% in which they needed it but could not be met (unmet need). Objectives: To determine the effect of health education by demonstration method and video playback media in enhancing knowledge and decision making to use contraception in the unmet need family planning. Methods: The study design was using pre-experiment with one group pretest-posttest design. The sampling technique was purposive sampling which found a sample of 46 unmet need women of reproductive age. Before and after getting health education by demonstration method and video playback media were given questionnaires about their knowledge level and 2 weeks after then were given interviewed to determine their decision to use contraception. The data analysis to find out the effect of health education by demonstration method used paired t-test and the data analysis to find out the decision making to use contraception used chi-square test. Results: the test results in enhancing knowledge obtained paired t-test count value of -7.8375, Cl g5% (2,730501 to -1,610962) and -2.170732 mean of the differences (p-value 0.000). the results in decision making to use contraceptionobtained chi-square value of 4.1938 and CI 95% 0,081 to 0,310, (p-value 0,1228).